(untitled) (Boletin Médico de Postgrado, 2020)
An experimental simple blind controlled clinical trial was carried out to evaluate muscle relaxation and predictors of difficult airway in patients scheduled for general surgery at the Hospital Central Universitario Dr. Antonio María Pineda. The sample consisted of 100 patients randomly distributed into four groups of 25 patients each. Patients from the Experimental-1 (E-1) and Control-1 (C-1) groups received 0.6 mg/kg of the neuromuscular blocking agent Rocuronium Bromide while Experimetal-2 (E-2) and Control-2 (C-2) patients received a dosage of 1 mg/kg. Average age of participants was 34.8 ± 9.8 years. Predictors of difficult airway in E-1 and E-2 were sternomental distance (32% and 42%, thyromental distance (24% and 40%), interincisive distance class 1 (88% and 92%), neck circumference > 40 cm (16% and 8%), Mallampati (88% and 40%), atlanto-occipital extension (28% and 20%) and mandibular protrusion (28% and 20%). In 72% and 80% of patients from the E and C groups there was not an additional attempt of orotracheal intubation (OTI); the time invested to reach the OTI was less than one minute in 64% of patients from the C-2 and 72% of the E-2. There are statistically significant differences between the number of attempts to reach the OTI, presence of predictors of difficult airway and the dose of Rocuronium Bromide which means that as the drug dosage increases, there is a greater possibility of success in the OTI, even when predictors of difficult airway are present.